Sk-Greedy: A Heuristic Scheduling Algorithm for Wireless Networks under the SINR Model - Fulber-Garcia, Vinicius; Camargo, Fábio Engel; Duarte Jr., Elias P. (Anais do Workshop on Security, Privacy and Reliability on Wireless Sensing Networks (WSENSING), 2022)
Recent advances in networking technologies such as massive Internet-of-Things and 6G-and-beyond cellular networks indicate a trend towards increasingly dense wireless communications. A wireless communication channel is a shared medium that demands access control, such as proper transmission scheduling. The SINR model can improve the performance of ultra-dense wireless networks by taking into consideration the effects of interference to allow multiple simultaneous transmissions in the same coverage area. However, finding the shortest schedule in wireless networks under the SINR model is an NP-hard problem. In this work, we present a greedy heuristic algorithm to solve that problem. The proposed solution, called Sk-Greedy (Stochastic k Greedy) algorithm produces a complete transmission schedule optimizing size, with the purpose of increasing the number of simultaneous transmissions (i.e., spatial reuse) thus allowing devices to communicate as frequently as possible. Simulation results are presented, including comparisons of Sk-Greedy with the optimal algorithm. Results confirm that the solution requires short execution times to produce near-optimal schedules.